Data warehousing and knowledge discovery : 10th International Conference, DaWak 2008 Turin, Italy, September 1-5, 2008, Proceedings - DaWaK 2008 (2008 : Turin, Italy); Song, Il-Yeol; Eder, J. (Johann), 1958-; Nguyen, Tho Manh (Berlin : Springer, 2008)
57